Organizing: An Islamic Perspective - Mohiuddin, Md Golam; Yusof, Gaffar Olanrewaju; Bulbul, Afroza (Global Disclosure of Economics and Business, 2013)
The issue of organizing and orderliness is paramount in Islam, it connotes an act of placing things in its proper place which is otherwise known as Hikmah (wisdom) in Islamic term. Today many organization exist, but are not aware of the act of organizing, according to Islamic perspective. Some people equate some Muslims or Islamic NGOs with the true Islamic act of governing this could be misconception on their part. Hence this study wishes to elucidate on act or organizing according to the injunctions of Allah and the practice of the holy prophet. This study employs documentary/library research method and data were collected through both primary and secondary sources. It is found from the study that Islam has its own perfect way of carrying out its organizational function as exemplified by the holy prophet which aims at improving the quality of life and the welfare of the society. It is now the hopes of all nations to direct attention to the way Islam portrayed organizational management and have a fruitful goal in this world and the hereafter. JEL Classification Code: M12; M54